Implementasi Perlindungan Data Pribadi Berdasarkan Undang-Undang Nomor 11 Tahun 2020 - Aulia Alayna Suvil; Firdaus Firdaus; M. Arif Ramadhan; Wanda Darma Putra; Dwi Putri Lestarika (Pusat Riset dan Inovasi Nasional, 2024)
The protection of personal data is becoming increasingly important in today's digital era, where information and communication technology is rapidly advancing. This raises the risk of data breaches that can have negative impacts, ranging from identity theft to harassment. The personal data protection law has become crucial for regulating the management and protection of such data, with the aim of providing a clear legal framework. Personal data protection includes the definition and scope of personal data as well as fundamental principles such as transparency, limitation of use, and data security. The regulation of personal data protection in Indonesia has evolved over time, with Law Number 11 of 2020 concerning Information and Electronic Transactions serving as a more comprehensive legal foundation. This research employs a descriptive approach, document analysis, and previous studies. Data analysis is conducted qualitatively to describe the implementation of the Personal Data Protection Law in Indonesia as well as the factors influencing it. The implementation of this law faces challenges, such as the gap between policy formulation and its execution, a lack of public awareness, and inadequate infrastructure. However, supporting factors like public campaigns and infrastructure improvements can strengthen the implementation of the law. Despite the challenges, the implementation of the Personal Data Protection Law in Indonesia can be improved through increased public awareness, investment in infrastructure, and collaboration among stakeholders. This recommendation is expected to effectively strengthen personal data protection in Indonesia.